Peningkatan Daya Guna Sampah Botol Plastik sebagai Media Tanam Berkelanjutan di RA Miftahul Huda, Kota Batu - Kartika Sari, Arista Fauzi; Hanafi, Hanafi; M. Ayyub; Kusprihatining, Dina; Ajron, Maghfirotun; Rizkyana, Enggar; Valentina, Anggita; Prayoga, Katon; Maulinda, Imelda; Ramadhany, Mohamad; Oktavian, Odhe; Deah, Aviyanti (Bhumiputra: Jurnal Penelitian dan Pengabdian Masyarakat Global, 2025)
This program is an effort to reduce plastic bottle waste by managing plastic bottles used become a pot so it can reused and for environment around. This program is also a goal to introduce procedures for planting ornamental plants in plastic bottle media and overcoming existence of pollution and damage the environment that caused from throw away rubbish plastic carelessly. Implementation of the cycle program bottle plastic this in progress in the first day and carried out in Giripurno Village with students of Miftahul Huda Kindergarten. Some of the benefits of this activity in addition to inviting targets to care about the environment, this activity can hone the creativity of Miftahul Huda's Kindergartern students as one of the learning media for Miftahul Huda's children regarding the use of waste and the cultivation of ornamental plants.